The Craft of Scientific Writing - Alley, Michael (Springer New York, 2018)
The Craft of Scientific Writing is designed to help scientists and engineers - both professionals already active in the disciplines as well as students preparing to enter the professions - write about their work clearly and effectively. Written for use as a text in courses on scientific writing, the book includes many useful suggestions about approaching a wide variety of writing tasks from journal papers to grant proposals and from emails to formal reports, as well as a concise guide to style and usage appropriate for scientific writing. Also useful for self-study, the book will be an important reference for all scientists and engineers who need to write about their work. With this new and updated fourth edition, while most technical writing texts have gotten larger over the years, this one has streamlined, to provide busy readers with the essence of what distinguishes the style of the best scientific documents. With this new edition, readers will learn not just how to organize information, but how to emphasize the key details of that information. Also, readers will not just learn how to cast their ideas into precise and clear sentences, but how to connect these sentences in an energetic fashion. In the section on language, the new edition goes into much depth about how to make connections between ideas: an important issue that few technical writing texts address. Moreover, the new edition integrates the discussion of illustrations with language because those two aspects of style are so intertwined. Finally, the new edition does a better job of explaining how to make the process of writing more efficient. From a review of the first edition: "A refreshing addition to a genre dominated by English teacher-style textbooks. Instead of listing rules that constrain writers, the book uses examples to lay out the path to successful communication ... Especially helpful (and entertaining) is the chapter on the writing process. Anyone who has spent more time avoiding a writing task than actually doing it will appreciate Alley's tips." -Dr. Ellen Ochoa, Deputy Director of Flight Crew Operations, Johnson Space Center.